Process evaluation of the midwifery initiated oral health-dental service program: Perceptions of midwives in Greater Western Sydney, Australia. Issue 2 (April 2019) - Dahlen, Hannah G.; Johnson, Maree; Hoolsema, Julia; Norrie, Tiffany Patterson; Ajwani, Shilpi; Blinkhorn, Anthony; Bhole, Sameer; Ellis, Sharon; Srinivas, Ravi; Yaacoub, Albert; Milat, Andrew; Skinner, John; et al.
Abstract: Background: Despite links between poor maternal oral health, adverse pregnancy outcomes and early childhood decay there is limited emphasis on maternal oral health in Australia. To address this, the Midwifery Initiated Oral Health Dental Service (MIOH-DS) program was developed in collaboration with the Australian College of Midwives. Aims: To undertake a process evaluation and explore perceptions of midwives involved in the MIOH-DS program to determine its practicability, acceptability and feasibility if it were to be up-scaled and implemented into clinical practice. Methods: Qualitative content analysis was undertaken on data from three focus groups with 21 midwives. Findings: Midwives generally found the MIOH-DS to be acceptable and feasible with potential for widespread scalability. The trust women had in midwives was an important factor in gaining women's attention about oral health in pregnancy. The program assisted in increasing midwives' knowledge and awareness, though some felt it was outside their scope of practice. The oral health assessment tool was acceptable to midwives but some concerns were expressed about undertaking a visual oral inspection. Most midwives stated they were now confident with referring individuals to a dentist. Significant barriers to widespread implementation included the cost of dental care and the continued lack of awareness and misconceptions pregnant women had towards oral health. Conclusion: Midwives found the MIOH-DS to be acceptable and feasible which are two important barriers to potential implementation at scale. Misconceptions over the importance of oral health by women and cost of accessing dental services still need resolving.